Dysmotility in Eosinophilic Esophagitis - Chai, Charmaine; Krishnan, Usha (Frontiers in Pediatrics, 2022)
• Eosinophilic esophagitis (EoE) is a chronic inflammatory disease resulting from antigen exposure which is rapidly rising in prevalence worldwide. Characterised by esophageal dysfunction and mucosal inflammation with eosinophils, eosinophilic esophagitis presents with a wide range of symptoms, from food refusal and vomiting in younger children to dysphagia and chest pain in adults. Although the diagnosis of EoE is dependent on histologic changes of hyper eosinophilia, this does not always correlate with symptom severity. Multiple studies have reported that EoE patients report dysphagia in the presence of normal endoscopies and biopsies and with no discernible anatomical lesions, raising the possibility of an underlying esophageal dysmotility. High resolution esophageal manometry, functional luminal imaging planimetry and endoscopic ultrasound have all contributed to a better understanding of the motility of the esophagus, with multiple hypotheses for the cause of dysphagia in EoE emerging. This review will look at the types of motor disturbances, the pathophysiological basis of dysmotility, and how best to investigate esophageal function in EoE. Although currently manometry, impedance planimetry and endoscopic ultrasound are not routinely used for either the diagnosis or follow-up in the management of EoE, future studies on the assessment of esophageal biomechanics (motility and compliance) could potentially help tailor therapy in these patients.